Note from Phoebe Hearst to Julia Morgan - Phoebe A. Hearst::::::author:::
Correspondence from Phoebe Hearst to Julia Morgan. Hearst thanks Morgan for the Christmas gift and wishes Morgan happiness and blessings during the New Year.